Effect of endometriosis on implantation rates when compared to tubal factor in fresh non donor in vitro fertilization cycles - Neeta Singh; Kusum Lata; Moumita Naha; Neena Malhotra; Abhinash Tiwari; Perumal Vanamail (Wolters Kluwer Medknow Publications, 2014)
Objective : The objective of the following study is to compare the outcome of in vitro fertilization and embryo transfer (IVF-ET) in women with endometriosis and tubal-factor infertility. Design : Retrospective study. Setting : Tertiary referral hospital, assisted reproductive technologies unit. Materials and Method : The study group consisted of 78 women diagnosed with advanced stage endometriosis. The control group included 100 women with tubal-factor infertility. These groups were retrospectively analyzed regarding stimulation, fertilization, embryo development, implantation and pregnancy outcome. Intervention (S) : Controlled ovarian hyperstimulation and IVF-ET. Results : Lower oocyte yield with lower fertilization rate were found in women with endometriosis compared with tubal-factor control subjects. However, no differences were found in cleavage, implantation and clinical pregnancy rates between the endometriosis and tubal-factor groups. Conclusions : Our results showed that women with endometriosis have a lower oocyte yield and lower fertilization rate compared with women with tubal-factor infertility. However, once the oocyte is fertilized, it seems that the embryo has a normal chance of implantation, leading to similar pregnancy rates and adequately treated women with endometriosis have equal chances of conception as seen with tubal-factor infertility.